Sea star-inspired recombinant adhesive proteins self-assemble and adsorb on surfaces in aqueous environments to form cytocompatible coatings. (August 2020) - Lefevre, Mathilde; Flammang, Patrick; Aranko, A. Sesilja; Linder, Markus B.; Scheibel, Thomas; Humenik, Martin; Leclercq, Maxime; Surin, Mathieu; Tafforeau, Lionel; Wattiez, Ruddy; Leclère, Philippe; Hennebert, Elise
Abstract: Sea stars adhere to various underwater substrata using an efficient protein-based adhesive secretion. The protein Sfp1 is a major component of this secretion. In the natural glue, it is cleaved into four subunits (Sfp1 Alpha, Beta, Delta and Gamma) displaying specific domains which mediate protein-protein or protein-carbohydrate interactions. In this study, we used the bacterium E. coli to produce recombinantly two fragments of Sfp1 comprising most of its functional domains: the C-terminal part of the Beta subunit (rSfp1 Beta C-term) and the Delta subunit (rSfp1 Delta). Using native polyacrylamide gel electrophoresis and size exclusion chromatography, we show that the proteins self-assemble and form oligomers and aggregates in the presence of NaCl. Moreover, they adsorb onto glass and polystyrene upon addition of Na + and/or Ca 2+ ions, forming homogeneous coatings or irregular meshworks, depending on the cation species and concentration. We show that coatings made of each of the two proteins have no cytotoxic effects on HeLa cells and even increase their proliferation. We propose that the Sfp1 recombinant protein coatings are valuable new materials with potential for cell culture or biomedical applications. Statement of Significance: Biological adhesives offer impressive performance in their natural context and, therewith, the potential to inspire the development of advanced biomaterials for an increasing variety of applications in medicine or in material sciences. To date, most marine adhesive proteins that have been produced recombinantly in order to develop bio-inspired adhesives are small proteins from mussels and barnacles. Here, we produced two multi-modular proteins based on the sequence of Sfp1, a major protein from sea star adhesive secretion. These two proteins comprise most of Sfp1 functional domains which mediate protein-protein and protein-carbohydrate interactions. We characterized the two recombinant proteins with an emphasis on functional characteristics such as self-assembly, adsorption and cytocompatibility. We discuss their potential as biomaterials. Graphical abstract: Image, graphical abstract